Antimicrobial effectiveness and Ag+ release in antimicrobial-modified PMMA: A systematic review (Research, Society and Development, 2024)
Silver, a long-term ionic release antimicrobial, is incorporated into polymethylmethacrylate (PMMA) in order to reduce bacterial adhesion to polymeric materials and increase the longevity of rehabilitation, given the prevalence of pathologies. The aim was to answer: "What is the correlation between ionic release and antimicrobial activity of acrylic resins incorporated with silver?". The search strategy was applied to the PubMed, ScienceDirect, Embase and Scopus databases. The articles were selected in two phases according to eligibility criteria. The risk of bias was assessed using the quasi experimental studies (non-randomized experimental studies) tool from the Joanna Briggs Institute (JBI). A total of 538 articles were found in the databases, of which 28 were duplicated and were excluded. After first reading, 6 studies were selected for full reading, 5 of which made up this review. Silver was evaluated in different incorporations, which had proven antimicrobial efficacy, given its ionic release. No meta-analysis was carried out due to the heterogeneity of the data. The included studies showed a directly proportional correlation between ionic release and antimicrobial activity in PMMA incorporated with silver-containing agents.